Menjelajahi Gaya Komunikasi Guru Sekolah Dasar dan Strategi Mereka dalam Mengatasi Hambatan Komunikasi di Kelas Bahasa Inggris - Gardana, Aldika; Ashaf, Abdul Firman; Kartika, Tina; Aiyanti, Nina Yudha; Besar, Ibrahim (Limas PGMI, 2025)
Teachers' communication styles are crucial in facilitating language acquisition among students. It is a fundamental component of the learning process that shapes students' overall success in acquiring a new language. This study aims at finding out communication styles the elementary school teachers utilize in English classes, and strategies the elementary school teachers use in overcoming communication barriers in English classes. This study employed a qualitative approach.  It used questionnaires and interviews to collect the data. To analyze the data gained from the questionnaires, the researcher used the rubric of the UFS Communication Style Questionnaire. The researcher used reflexive thematic analysis by Braun & Clarke to analyze the data gained through the interviews. The respondents in this research were all (five) English teachers at SDIT Izzuddin Palembang, South Sumatra. The findings show that 80% of English teachers are categorized as having considerate communication style in their English classes. Only 20% is categorized as having direct communication style in her English class, and no English teacher is categorized as having spirited and systematic communication styles. The strategies the teachers used for overcoming communication barriers are active clarification and repetition, speech and delivery modification, interactive confirmation and feedback, and engagement and motivational support.